An assessment of the recruitment, diversity strategies and initiatives used to promote and retain undergraduate students : the case study of Stellenbosch University - Siebritz, Ubenicia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2012.